Intellectual property as a complex adaptive system : the role of IP in the innovation society - Kamperman Sanders, Anselm; Moerland, Anke (European intellectual property institutes network series, 2021)
"This incisive book examines the role of Intellectual Property (IP) as a complex adaptive system in innovation and the lifecycle of IP intensive assets. Discussing recent innovation trends, it places emphasis on how different forms of intellectual property law can facilitate these trends. Inventors and entrepreneurs are guided through the lifecycle of IP intensive assets that commercialise human creativity. Utilising a range of sector-specific, interdisciplinary and actor-focused approaches, each contribution offers suggestions on how Europe's capacity to foster innovation-based sustainable economic growth can be enhanced on a global scale. This comprehensive book addresses the role of IP in public-private partnerships and business transactions and further explores how IP law can uphold distributive justice in the innovation society. Chapters span a range of topics of great societal interest, including standard essential patent licensing in the Internet of Things, patent quality concerns under competition law and the role of market-driven and legislative solutions to online music licensing. Intellectual Property as a Complex Adaptive System will be a key resource for students and scholars of IP law, innovation and economics. It will also be vital reading for practitioners, knowledge-intensive industry representatives and innovation and technology transfer specialists"--